Carbene derived diradicaloids – building blocks for singlet fission?. Issue 28 (2nd July 2018) - Messelberger, Julian; Grünwald, Annette; Pinter, Piermaria; Hansmann, Max M.; Munz, Dominik
Abstract : Carbene–bridge–carbene ensembles: tunable diradicaloids for singlet fission? Abstract : Organic singlet diradicaloids promise application in non-linear optics, electronic devices and singlet fission. The stabilization of carbon allotropes/cumulenes (C1, C2, C4 ) by carbenes has been equally an area of high activity. Combining these fields, we showed recently that carbene scaffolds allow as well for the design of diradicaloids. Herein, we report a comprehensive computational investigation (CASSCF/NEVPT2; fractional occupation DFT) on the electronic properties of carbene–bridge–carbene type diradicaloids. We delineate how to adjust the properties of these ensembles through the choice of carbene and bridge and show that already a short C2 bridge results in remarkable diradicaloid character. The choice of the carbene separately tunes the energies of the S1 and T1 excited states, whereas the bridge adjusts the overall energy level of the excited states. Accordingly, we develop guidelines on how to tailor the electronic properties of these molecules. Of particular note, fractional occupation DFT is an excellent tool to predict singlet–triplet gaps.